2011
DOI: 10.1007/978-1-61779-024-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Generation, Validation, and Application of Phosphosite-Specific Antibodies

Abstract: Protein phosphorylation is a universal key posttranslational modification that affects the activity and other properties of intracellular proteins. Phosphosite-specific antibodies can be produced as polyclonals or monoclonals in different animal species, and each approach offers its own benefits and disadvantages. The validation of phosphosite-specific antibodies requires multiple techniques and tactics to demonstrate their specificity. These antibodies can be used in arrays, flow cytometry, and imaging platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 110 publications
0
22
0
2
Order By: Relevance
“…As truly phosphospecific mAb generation is challenging (34), it may be rare to find such clones with midpicomolar 1:1 binding affinity that subsequently aid the generation of high-quality crystals. The high-resolution pT231/ pS235_1 co-crystal structure showed that the mechanism of interaction used by the antibody does not fit strictly into any one of the classical protein-, peptide-, or hapten-binding modes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As truly phosphospecific mAb generation is challenging (34), it may be rare to find such clones with midpicomolar 1:1 binding affinity that subsequently aid the generation of high-quality crystals. The high-resolution pT231/ pS235_1 co-crystal structure showed that the mechanism of interaction used by the antibody does not fit strictly into any one of the classical protein-, peptide-, or hapten-binding modes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the recognition of phosphopeptides by protein kinases and phosphatases has been extensively studied (33), there are only a handful of papers describing anti-phosphopeptide antibodies that were selected via display technologies (34,35). Furthermore, none of the phosphopeptide-antibody complexes currently described in the literature have been structurally characterized beyond in silico modeling and CDR mutagenesis (36 -38).…”
mentioning
confidence: 99%
“…Rodent immunization approaches often fail or produce lowaffinity antibodies. This is because the peptide epitopes containing PTMs are weak immunogens in mice (22), PTMs undergo rapid degradation in vivo regardless of the immunization route (23), and Bcell response shows an affinity ceiling (24,25). Screening recombinant antibody libraries in vitro is a promising alternative.…”
Section: Introductionmentioning
confidence: 99%
“…9 Unfortunately, this strategy is labor-intensive and low-throughput, often requiring extensive purification and screening to generate high-affinity reagents. 10 For many complex glycan targets, this may not be feasible due to the difficulty of obtaining homogeneously glycosylated antigen. Additionally, many glycans and glycopeptides tend to be T-independent antigens and elicit relatively low affinity IgM subtype antibodies instead of the preferred high affinity IgG subtypes.…”
mentioning
confidence: 99%